Deciphering the sensing of alpha-amyrin acetate with hs-DNA: a multipronged biological probe - Pansare, V. Amol; Shedge, Amol A.; Sonawale, Maryappa C.; Pansare, V. Shubham; Mahakal, Akshay D.; Khairkar, Shyam R.; Chhatre, Shraddha Y.; Kulal, Dnyaneshwar K.; Patil, Vishwanath R. (RSC Advances, 2022)
In this study, we focus on the biomimetic development of small molecules and their biological sensing with DNA. The binding of herring sperm deoxyribonucleic acid (hs-DNA) with naturally occurring bioactive small molecule alpha-amyrin acetate (alpha-AA), a biomimetic - isolated from the leaves of Ficus (F.) arnottiana is investigated. Collective information from various imaging, spectroscopic and biophysical experiments provides evidence that alpha-AA is a minor groove sensor of hs-DNA and preferentially binds to the A-T-rich regions. Interactions of different concentrations of small molecule alpha-AA with hsDNA were evaluated via various analytical techniques such as UV-Vis, circular dichroism (CD) and fluorescence emission spectroscopy. Fluorescence emission spectroscopy results suggest that alpha-AA decreases the emission level of hsDNA. DNA minor groove sensor Hoechst 33258 and intercalative sensor EB, melting transition analysis (T-M) and viscosity analysis clarified that alpha-AA binds to hs-DNA via a groove site. Biophysical chemistry and molecular docking studies show that hydrophobic interactions play a major role in this binding. The present research deals with a natural product biosynthesis-linked chemical-biology interface sensor as a biological probe for alpha-AA: hs-DNA.

Development of reversed-phase HPLC method for purity assessment of aryl porphyrins and their metal complexes - Ujagare, Ashish Mohan; Uzagare, Matthew C.; Ghogare, Bhausaheb N.; Gupta, Lokesh Kumar; Wadgaonkar, Prakash P.; Patil, Vishwanath R.; Donde, Kamini J. (SSC Plus, 2025)
A gradient reversed-phase HPLC method was developed for in-process monitoring of the formation of aryl porphyrins and their corresponding metallo-aryl porphyrins. The method also proved effective for determining their quantitative purity. Optimal results achieving proper peak shape and separation of peaks in the chromatogram were obtained using C8 column and gradient of acetic acid-water and acetonitrile. The detector wavelength was selected for simultaneous detection of starting materials and products for in-process analysis for conversion of aryl aldehydes to corresponding tetraaryl porphyrins at 254 nm and metallo-aryl porphyrins formation from tetraaryl porphyrin at 413 nm, respectively; while the purity of products could be determined at 413 nm. The developed method is efficient, versatile, accurate, and easy to carry out and could serve as a handy tool for the reaction monitoring and determination of purity in the processes development of synthetic porphyrins and metalloporphyrins.